Social Media and Non-Personal Communication for Increasing Brand Equity and Their Implications towards Customer Value - Taufik Zulfikar; Adhi Al Hadi Haqq; Didin Saepudin (RIRAI Publisher, 2022)
Identifying, creating and delivering customer value will gain a competitive advantage. Providing benefits and reducing costs/costs is an effort to increase value. Reducing the sacrifice the company can do marketing through social media and non-personnel communication because this can increase brand equity in customers. This study aims to analyze and prove the effect of social media and non-personnel communication on brand equity which has an impact on customer value. The research method used a survey to 200 smartphone customers in Bandung where respondents were given 29 closed questions with ordinal 1 to 5. The analytical tool used was path analysis. The results show that the respondent's perception of the customer value variable is in the fairly good to good category. The results also show that there is an influence of social media and non-personnel communication on brand equity either partially or simultaneously, the results also show that there is an influence of brand equity on customer value, there is an influence of social media and non-personnel communication on customer value partially